Sea anemones (Cnidaria: Actiniaria, Corallimorpharia, Ceriantharia, Zoanthidea) from marine shallow-water environments in Venezuela: new records and an updated inventory. Issue 1 (December 2016) - González-Muñoz, Ricardo; Simões, Nuno; Guerra-Castro, Edlin; Hernández-Ortíz, Carlos; Carrasquel, Gabriela; Mendez, Enio; Lira, Carlos; Rada, Martin; Hernández, Iván; Pauls, Sheila; Croquer, Aldo; Cruz-Motta, Juan
Abstract Background This study compiles the diversity of sea anemones in different shallow habitats (i.e. rocky shores, coral reefs, mangroves and sandy bottoms) in several locations of Venezuela, including the most important marine reserves of Venezuela: Morrocoy National Park, Mochima National Park, Archipiélago de Los Roques National Park, Laguna de La Restinga National Park, Isla de Cubagua, and Chichiriviche de la Costa. Results Twenty-six species of sea anemonessensu lato were documented, from which only two actiniarian species are newly recorded in Venezuela. In addition, specimens of the scientific collection of the Museo Oceanológico Hermano Benigno Román, of Isla de Margarita, Venezuela, were examined and its taxonomic status updated. Conclusions The diversity of sea anemones in Venezuela is updated to 44 species. An illustrated guide of living specimens and short descriptions of the external anatomy of the specimens is included to facilitate sea anemone species identification in the field and to provide a base line for ecological studies that require accurate identification to species level.